Use of 3D domain swapping in constructing supramolecular metalloproteins. Issue 91 (29th October 2021) - Hirota, Shun; Mashima, Tsuyoshi; Kobayashi, Naoya
Abstract : Many metalloproteins can undergo 3D domain swapping. This future article summarizes in vitro and in vivo formation of supramolecular metalloproteins through 3D domain swapping. Abstract : Supramolecules, which are formed by assembling multiple molecules by noncovalent intermolecular interactions instead of covalent bonds, often show additional properties that cannot be exhibited by a single molecule. Supramolecules have evolved into molecular machines in the field of chemistry, and various supramolecular proteins are responsible for life activities in the field of biology. The design and creation of supramolecular proteins will lead to development of new enzymes, functional biomaterials, drug delivery systems, etc.; thus, the number of studies on the regulation of supramolecular proteins is increasing year by year. Several methods, including disulfide bond, metal coordination, and surface–surface interaction, have been utilized to construct supramolecular proteins. In nature, proteins have been shown to form oligomers by 3D domain swapping (3D-DS), a phenomenon in which a structural region is exchanged between molecules of the same protein. We have been studying the mechanism of 3D-DS and utilizing 3D-DS to construct supramolecular metalloproteins. Cytochrome c forms cyclic oligomers and polymers by 3D-DS, whereas other metalloproteins, such as various c -type cytochromes and azurin form small oligomers and myoglobin forms a compact dimer. We have also utilized 3D-DS to construct heterodimers with different active sites, a protein nanocage encapsulating a Zn–SO4 cluster in the internal cavity, and a tetrahedron with a designed building block protein. Protein oligomer formation was controlled for the 3D-DS dimer of a dimer-monomer transition protein. This article reviews our research on supramolecular metalloproteins.